Hubungan Efikasi Diri dan Dukungan Sosial dengan Kecemasan dalam Menghadapi Dunia Kerja pada Mahasiswa Tingkat Akhir - Vincensius Kardinal; Andik Matulessy; Nindia Pratitis (Journal of Medical Practice and Research, 2025)
This study aimed to examine the relationship between self-efficacy and social support with anxiety in facing the world of work among final-year university students. A quantitative approach with a correlational design was employed. The participants consisted of 107 final-year students in Surabaya who were selected using incidental sampling. Data were collected using three psychological scales measuring anxiety toward the world of work, self-efficacy, and social support, all of which demonstrated satisfactory validity and reliability. Data analysis was conducted using multiple linear regression to examine both simultaneous and partial relationships among variables. The results indicated that self-efficacy was significantly and negatively associated with anxiety, suggesting that students with higher confidence in their abilities experienced lower levels of anxiety when facing employment challenges. Social support was also found to have a significant negative relationship with anxiety, indicating its protective role in reducing psychological distress. Simultaneously, self-efficacy and social support significantly contributed to the prediction of anxiety, with self-efficacy showing a stronger influence. These findings highlight the importance of strengthening internal beliefs and external support systems to reduce anxiety related to career transitions among final-year students.